Linearly coupled transverse vibrations of tensioned bolts. (October 2022) - Sah, Si Mohamed; Thomsen, Jon Juel; Tcherniak, Dmitri
In this study an analytical model for linear coupling between the two perpendicular transverse vibration modes in a tightened bolt is presented. The model shows an excellent fit with the experimental data suggesting that the coupling is dominantly linear. An experiment is performed to support the linearity claim. Two physical scenarios that could justify the theoretical model is given, one scenario involves asymmetric boundary stiffness and the other one measurements imperfection in location. This work is motivated by its application in structural health monitoring techniques, in particular those based on measuring transverse vibrations of bolts and other beam-like components.